REKONSTRUKSI NALAR ARAB KONTEMPORER MUHAMMAD ‘ABED AL-JABIRI - Muhammad Iqbal Juliansyahzen (Indonesian Journal of Islamic Law, 2018)
The condition of Arab reason has experienced a severe stagnation, resulting in the Arab world lagging behind the increasingly developed modern rationality. This fundamental problem became a major challenge for M. Abed al-Jabiri in his effort to awaken Arab reason from its long intellectual slumber. Jabiri argues that the Arab and Islamic worlds should not turn a blind eye to developments in the West; rather, there should be a critical dialogue and a dialogue of civilizations. Jabiri’s project in seeking authenticity represents a significant intellectual endeavor to advance the Arab-Islamic world and to avoid uncritical claims of cultural dominance, whether originating from classical Islamic tradition or Western modernity. He strongly emphasizes the epistemology of contemporary Arab thought as the primary path for engaging with modernity. In his attempt to reconstruct contemporary Arab reason, Jabiri classifies epistemology into three modes: bayānī, burhānī, and ‘irfānī. However, this classification has generated considerable criticism; for instance, it is argued that such a division leads to fragmentation within the intellectual self.